2022
DOI: 10.1159/000524919
|View full text |Cite
|
Sign up to set email alerts
|

Emerging New Therapeutics for Retinoblastoma

Abstract: Background: Over the last few decades, chemotherapy has become the main treatment of retinoblastoma, delivered through various routes: intravenous (IVC), intra-arterial (IAC), and intravitreal (IvitC). Despite its efficacy, chemotherapy related toxicity (ocular and systemic) and recurrences due to resistant tumor clones are common, highlighting the need for novel therapeutic agents. Summary: Recent advances in our understanding of the molecular drivers of Rb1 tumorigenesis and mechanisms of tumor resistance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…In preclinical studies, the topical instillation of cell-penetrating peptide-conjugated melphalan has demonstrated efficacy comparable to intravitreal melphalan, with the added advantage of reducing the risk of metastasis [59]. Furthermore, the current trend in research has shifted toward exploring non-chemotherapeutic alternatives, including targeting specific molecular pathways such as MDMX-p53 and OTX2, immunotherapy, and genetic modulation through oncolytic adenoviruses [56,60,61]. These innovative approaches signify a broader exploration of treatment avenues beyond traditional chemotherapy.…”
Section: 2)mentioning
confidence: 99%
“…In preclinical studies, the topical instillation of cell-penetrating peptide-conjugated melphalan has demonstrated efficacy comparable to intravitreal melphalan, with the added advantage of reducing the risk of metastasis [59]. Furthermore, the current trend in research has shifted toward exploring non-chemotherapeutic alternatives, including targeting specific molecular pathways such as MDMX-p53 and OTX2, immunotherapy, and genetic modulation through oncolytic adenoviruses [56,60,61]. These innovative approaches signify a broader exploration of treatment avenues beyond traditional chemotherapy.…”
Section: 2)mentioning
confidence: 99%